Improving of Traffic Capacity for Congested Square inBaghdad City - A. Awad, Hamid (Iraqi Journal of Civil Engineering, 2008)
Abstract :The increase in traffic volumes at intersections is one of the important problems thatmakes difficulties in the traffic operation management and movement then leads to trafficcongestion in these facilities.Capacity and level of service are important considerations and control points for theanalysis of intersections and evaluate the operation of the intersection.The present paper is dealing with the objectives of the evaluation of the capacity and thelevel of service at Al-Mat'haf square in Baghdad City, and development of alternativeimprovement strategies to overcome the traffic operation problems and to present a bestproposal to enhance the performance from the capacity point of view.To achieve these objectives, the traffic volumes data collection and geometric layout forAl-Mat'haf square that required for the traffic and geometrical analysis were gatheredmanually, while SIDRA traffic program is used for the requirements of traffic analysisprocess.It has been concluded that, fly over connect the direction arrived from Al-Tajneedintersection towards Damascus square is the best proposal to improve the capacity andtraffic operation ability of Al-Mat'haf squareKeywordsTraffic Capacity, Traffic Operation, Level of Service (LOS), Saturation Flow